THE EVOLUTION OF THE PRINCIPLE OF SEPARATION AND BALANCE OF THE POWERS OF THE STATE AND THE EXECUTIVE - Oana ŞARAMET (Bulletin of the Transilvania University of Braşov Series VII: Social Sciences • Law • Vol. 8 (57) No. 1 - 2015, 2015)
The theory and the separation of balance in the powers of the state, implemented at a constitutional level, either specifically or by identifying and organizing the powers, according to the “scheme” established by its advocates, has tried to create the best means possible to establish a moderate government. [12] The passing of time, political, legal and state developments reflected by the current constitution, constant attempts of the executive, especially the governments, to arrogate to itself more and more functions in the legislative field will also influence the evolution of this principle.
Keywords: principle; separation of powers; balance; executive; evolution